Analysis on Underlying Cryptocurrency Assets as Investment Instruments (A Case Study of Bitcoin, Ethereum, Tether and USDC) - Faizin, Mu’adil (Al-Huquq: Journal of Indonesian Islamic Economic Law, 2023)
Cryptocurrencies experienced a huge surge whose value reached more than US 191 million or Rp. 2.7 trillion. Interestingly, almost all types of cryptocurrencies do not have an underlying asset as a common underlying asset in ordinary investments. Bitcoin and Ethereum claims that its underlying asset is the coin miner charges from the amount of hardware and electricity used in the transaction. Tether and USDC claim that their underlying assets are in US dollars. This article examines Islamic law regarding the underlying assets in the form of coin mining fees and US Dollars. The questions that arise are, how is the study of Islamic law regarding the underlying asset in the form of coin mining fees and US Dollars? Furthermore, the ideal pattern of a cryptocurrency scheme that includes assets in the form of tangible goods refers to manafiul a’yan? This research uses the gate of legal philosophy approach, looks at the business scheme in terms of values and principles and then provides legal conclusions based on that assessment. From the research conducted, first, the underlying asset of coin mining costs cannot be said to be an underlying asset that is truly economically useful for coin owners, except for the technology access costs which are clearly experienced by all technologies. Second, the underlying asset in the form of US Dollars has clearer benefits, but this is contrary to Islamic law. Third, for the underlying asset in the form of tangible goods, ownership must always be included in every coin purchased.